2012
DOI: 10.1016/j.jpainsymman.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Does Health-Related Quality of Life Improve for Advanced Pancreatic Cancer Patients Who Respond to Gemcitabine? Analysis of a Randomized Phase III Trial of the Cancer and Leukemia Group B (CALGB 80303)

Abstract: Context Gemcitabine for advanced pancreas cancer (APC) is palliative and prognosis is poor, making health-related quality of life (HRQOL) particularly important. Objectives We evaluated HRQOL with the EuroQol EQ-5D™, in patients with APC participating in Cancer and Leukemia Group B (CALGB) 80303, a multicenter, double-blind, randomized trial comparing overall survival (OS) between two treatment arms, gemcitabine with bevacizumab, or gemcitabine with placebo. Methods A consecutive subsample of patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 21 publications
3
42
0
1
Order By: Relevance
“…Also in accordance with other studies. [15,[25][26][27][28][29]31,32] Otherwise, of our findings, there are other studies [24,30] who have concluded that Fol significantly reduces QOL impairment in patients with metastatic pancreatic cancer, because of the increased toxicity of Fol.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Also in accordance with other studies. [15,[25][26][27][28][29]31,32] Otherwise, of our findings, there are other studies [24,30] who have concluded that Fol significantly reduces QOL impairment in patients with metastatic pancreatic cancer, because of the increased toxicity of Fol.…”
Section: Discussionmentioning
confidence: 61%
“…Other authors also concluded that Gem did not improve QOL for patients who respond to treatment, so it did affect their emotional and functional status. [31,32] The functional well-being is also better in fol arm compared to Gem arm. Patients in fol arm claimed that it helped them to cope better with depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis therefore made use of the average utility value for stable disease (that is, 0.80) and the lower value from the range reported for progressive disease (that is, 0.73), given that the 8-week value would be representative of the patients in our model, being carried through progressive disease until death. Similarly, Romanus et al 11 reported the utility value for a partial response as 0.83, and that value was also incorporated into our model ( Table i).…”
Section: Os and Pfsmentioning
confidence: 93%
“…Similarly, the difference in pfs between the treatment groups was very minimal-2.87 months and 2.89 months for the Weibull and Kaplan-Meier curves respectively. 11 , who reported utilities for both stable and progressed pancreatic cancer patients treated with gemcitabine. In that study, patients with advanced pancreatic cancer participating in the Cancer and Leukemia Group B multicentre double-blind randomized 80303 trial, which compared os in two treatment arms (gemcitabine plus bevacizumab, gemcitabine plus placebo), were evaluated on their health-related qol using the EuroQol instrument (EQ-5D) at baseline and at 8 weeks.…”
Section: Os and Pfsmentioning
confidence: 99%